Contribution of genetic factors other than CFTR to disease severity in cystic fibrosis. Issue 12 (1st December 1998) - Hull, Jeremy; Thomson, Anne H
Abstract : BACKGROUND: Disease severity in patients with cystic fibrosis shows marked variability. Attempts to explain this phenotypic heterogeneity on the basis of CFTR genotype have had limited success. A study was undertaken to test the hypothesis that naturally occurring variants of the pro-inflammatory cytokine tumour necrosis factor alpha (TNF-α) and the detoxifying enzyme glutathione S-transferase M1 (GSTM1) could influence disease severity in cystic fibrosis. METHODS: Fifty three children with cystic fibrosis were studied. To allow for the effect of age, all clinical details were collected during the eighth year of age. The subjects were divided into groups, both according to the presence or absence of the TNF2 TNF-α -308 promoter polymorphism (n = 20), and by homozygosity for the null allele of GSTM1 (n = 26). RESULTS: Percentage predicted forced expiratory volume in one second (FEV1 ) and weight z scores were significantly lower in the TNF2 group (mean difference (95% confidence intervals) for FEV1 11.6% (1.7 to 21.5) and 0.59 (0.06 to 1.12) for weight z score). The Chrispin-Norman chest radiographic score was significantly higher and the Shwachman score was significantly lower in patients homozygous for the GSTM1 null allele. CONCLUSIONS: Two independent genetic factors have been identified which appear to influence disease severity in cystic fibrosis. These results support the contention that inflammation in cystic fibrosis contributes to tissue damage. Isolation of further such factors may lead to identification of patients at risk of more severe disease and allow targeted aggressive therapy in this group.